Cultural Differences in Mixed Emotions: The Role of Dialectical Thinking - Zheng, Wen; Yu, Ailin; Li, Disi; Fang, Ping; Peng, Kaiping (Frontiers in Psychology, 2021)
Who can feel both happy and sad at the same time, but not discomfort? This study aimed to investigate the cultural differences in mixed emotional experiences induced by conflict stimuli among American and Chinese undergraduate students. In total, 160 Americans and 157 Chinese watched 2 pieces of different valence advertisements (one predominantly positive and the other predominantly negative) that elicited mixed emotions, and had their feelings assessed through self-reported measures. Findings indicated the impact that cultural differences have in people’s mixed emotional experiences depends on the emotional components of the mixed emotional situations. The Americans and Chinese both experience a comparably intense mixture of emotions in different valence situations, but their discomfort toward conflicting stimuli are different. Further dialectical thinking may be a mechanism behind the influence of cultural differences in people’s mixed emotional experiences. Implications for emotion theory and research are discussed.